Groundwater quality is assessed by comparing pH, total dissolved solids (TDS), and electrical conductivity (EC) in wells in the Sabratha region (Libya): A field study. (Al-Farooq Journal of Sciences, 2026)
This study was conducted in the Sabratha area, 70 kilometers west of Tripoli, to evaluate the quality of groundwater wells in the region and compare them with local and international standards. Most residents of this area rely on groundwater wells for drinking water and agriculture, particularly in rural and semi-urban areas where surface water availability is limited for domestic, agricultural, and industrial uses. Water samples were collected from 30 wells distributed across different areas of the city between October and December 2018, and assigned the codes B1 to B30. Groundwater samples were collected 10 minutes after pumping to avoid unexpected changes in water properties, in accordance with standard procedures (APHA, 2015). All samples were collected in the morning using one-liter polyethylene bottles. The samples were transported to the laboratory on the same day as collection, and physical analyses were performed, including electrical conductivity (EC) and pH measurement, as well as chemical analyses such as total dissolved solids (TDS) and electrical conductivity (EC)).The results showed that the hydrogen ion concentration (pH) values ​​all ranged between 7.1 and 7.9 and did not exceed the permissible limits for drinking water according to Libyan standards. However, the TDS levels were high in most wells, exceeding the permissible limits according to Libyan drinking water standards. The highest value (9350 mg/L) was recorded in well B4, and the lowest value (590 mg/L) in well B16 (3). The results for electrical conductivity in the study samples were as follows: The highest value was in well number (4) and the lowest value was in well number (16) in the study area, which had the highest rates in the city center, Talil and Qalil area, which ranged between (μs/cm 9900) for sample (B4) and (μs/cm 9600) for sample (B3) and (μs/cm 9600) for sample (B25), respectively, where the conductivity exceeded the permissible limits for drinking water, which indicates the concentrations of dissolved salts, the proximity of the wells to seawater and the difference in the layers of the underground earth..
Keywords: Groundwater, pH, Total Dissolved Solids (TDS), Electrical Conductivity (EC))